2019
DOI: 10.17533/udea.iatreia.31
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencia de ansiedad preoperatoria y factores asociados en gestantes programadas a cesárea

Abstract: Objetivo: estimar la frecuencia de la ansiedad preoperatoria (AP) y los factores asociados enlas gestantes programadas con cesárea electiva.Métodos: estudio transversal en mujeres con embarazo de término sin actividad uterina nicomplicaciones médicas, quirúrgicas u obstétricas, realizado previo a la intervención de cesárea electiva, en Cartagena, Colombia. Participación anónima y voluntaria con consentimiento informado. Se aplicó un formulario de características sociodemográficas y la versión en español de la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…The odds of having preoperative anxiety are higher among women who had poor and moderate social support as compared to women having strong social support. The results of this study were supported by other studies conducted in Egypt, and Colombia [ 30 , 44 ]. This implies that strong social support plays a role in preventing illness, and promoting patient compliance with the given treatment, and reducing financial related anxiety [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The odds of having preoperative anxiety are higher among women who had poor and moderate social support as compared to women having strong social support. The results of this study were supported by other studies conducted in Egypt, and Colombia [ 30 , 44 ]. This implies that strong social support plays a role in preventing illness, and promoting patient compliance with the given treatment, and reducing financial related anxiety [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study suggested that the odds of preoperative anxiety among women who need more information about anesthesia and surgeries were 4.6 times higher than women who required no information. This finding was supported by studies conducted in Addis Ababa, and Nepal Similar to studies conducted in Addis Ababa [ 39 , 44 ]. This is because patients in need of comprehensive information may ask from non-anesthetist, the Internet, and neighbors with inadequate knowledge of anesthesia, which can lead to misunderstandings and fearful interpretations of surgery [ 17 ].…”
Section: Discussionsupporting
confidence: 79%